Preventive Effectiveness of Academic and Social Sanctions Against University Students Perpetrating Sexual Violence - Suardi, Suardi; Ramlan, Herdianty; Hashim , Shahrin Bin (FKIP - Universitas Riau, 2025)
Sexual violence in higher education remains a critical threat to student safety and institutional integrity. Yet, preventive strategies particularly academic and social sanctions have received limited empirical scrutiny from the student perspective. This study investigates students’ perceptions of the effectiveness of such sanctions in preventing campus sexual violence. Utilizing a convergent parallel mixed-methods design, data were collected through closed-ended questionnaires and semi-structured interviews at Universitas Muhammadiyah Makassar. Quantitative results reveal strong support for academic sanctions, including scholarship revocation (92.21%), suspension (88.31%), and expulsion (85.06%). Likewise, students endorse social sanctions such as public apologies, organizational exclusion, and the disclosure of perpetrators’ identities, seen as morally pressuring and socially stigmatizing. Thematic analysis of qualitative data highlights that students view sanctions as part of a broader institutional protection system one that hinges on safe reporting mechanisms, transparent procedures, and gender equality education. However, concerns persist over the inconsistency of institutional enforcement. The findings suggest that effective sexual violence prevention requires a multidimensional strategy combining regulatory discipline, cultural transformation, and participatory education. Methodologically, this study contributes through its triangulated approach, and theoretically, it affirms the dual function of sanctions as both deterrent and normative instruments in fostering a safer, more accountable academic environment.